Glutathione restores the mitochondrial redox status and improves the function of the cardiovascular system in old rats - Strutynska, Nataliіa; Goshovska, Yulia; Mys, Lidiia; Strutynskyi, Ruslan; Luchkova, Alina; Fedichkina, Raisa; Okhai, Iryna; Korkach, Yuliia; Sagach, Vadym (Frontiers in Physiology, 2023)
Aging is accompanied by cardiovascular disorders which is associated with an imbalance of pro- and antioxidant systems, the mitochondrial dysfunction, etc. Glutathione (GSH) plays a critical role in protecting cells from oxidative damage. The aim of the work was to study the effect of exogenous GSH on the redox status of mitochondria, the content of H2S and the function of the cardiovascular system in old rats. Experiments were performed on adult (6 months) and old (24 months) Wistar rats divided into three groups: adult, old and glutathione-treated old rats. Glutathione was injected intraperitoneally at a dose of 52 mg/kg. We investigated glutathione redox balance, H2S levels, oxidative stress, the opening of the mitochondrial permeability transition pore (mPTP), the resistance of isolated heart to ischemia/reperfusion in Langendorff model, endothelium-dependent vasorelaxation of isolated aortic rings, and cardiac levels of 3-MST, CSE, and UCP3 mRNA were determined using real-time PCR analysis. Our data shows that in old rats treated with glutathione, the balance of its oxidized and reduced form changes in the direction of a significant increase (by 53.6%) of the reduced form. Glutathione pretreatment significantly increased the H2S levels, mtNOS activity, and UCP3 expression which considered as protective protein, and conversely, significantly decreased oxidative stress markers (the rate of O2•- generation, the levels of H2O2, diene conjugates and malone dialdehyde, in 2.5, 2.3, 2 and 1.6 times, respectively) in heart mitochondria. This was associated with the inhibition mPTP opening and increased resistance of the isolated heart to ischemia/reperfusion in these animals. At the same time, in glutathione-treated old rats, we also observed restoration of endothelium-dependent vasorelaxation responses to acetylcholine, which were almost completely abolished by the NO-synthase inhibitor L-NAME. Thus, the pretreatment of old rats with glutathione restores the mitochondrial redox status and improves the function of the cardiovascular system.